The Maternal Nutrition and Knowledge Level in Stunting Children - Novita Indri Astuti; Listyaning Eko Martanti; Ida Ariyanti (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2020)
Stunting is nutrition based on height index according to age (TB / U) with a threshold (Z-core) -2 standard deviation (SD). Stunting in toddlers needs special attention because it can hamper children's physical and mental development. stunting is associated with an increased risk of morbidity and death as well as stunted growth in motor and mental abilities. This type of research is descriptive with sampling using a random sampling with a population of 79 respondents. Data were collected using a questionnaire and then explained and described the characteristics of each variable.The results showed that the mother's age at stunting toddlers was higher at healthy reproductive ages 20-35 yrs by 78.5% with more stunting mothers' education with 38.0% of elementary / middle school mothers' final educational status / parents' average toddler exposure income umr that is as much as 89.9% the level of knowledge of the mother is sufficient that is as much as 69.9% the mother's nutritional intake is still as much as 53.2%.Based on research shows that most of the knowledge level of mothers in stunting toddlers has sufficient knowledge and parenting mother nutrition in health centers bonang I is still lacking. From this research midwives are expected to be able to improve their competence by following training and the latest developments on antenatal care to improve service quality. Keywords : Stunting, Mother's Age, Education, Economic Status, Knowledge, Parenting Nutrition